Codebook for the PEQUIV file 1984-2011: CNEF variables with extended income information for the SOEP - Markus M. Grabka (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The PEQUV-File is based on the Cross-National Equivalent File (CNEF) with extended income information for the SOEP. This file comprises not only the aggregated income figures provided in the CNEF but also further single income components.
Keywords: 330